Penerapan postur tubuh yang ergonomis oleh mahasiswa tahap profesi Fakultas KedokteranGigiUniversitasHasanuddinselamaprosedurperawatan (Application of ergonomic posture by clinical dental students of Faculty of Dentistry Hasanuddin University during treatment procedure) - Windi Windi; Rasmidar Samad (DiscoverSys Inc., 2015)
In the daily work, dentists are required to performprecision in relatively small treatment areas,inside the mouth. We oftenfind a dentist who does his work with an awkward position in a relatively long time. Musculoskeletal disorders oftenoccur as a result of less ergonomic body position while working which occurs for a long time and repeatedly. The aim ofthis descriptive observational study was to determine the application of ergonomic posture by Hasanuddin Universityclinical dental student during treatment procedures. The ergonomic posture during treatment measures assessed by directobservation on 78 clinical students of Faculty of Dentistry using test of visual perception (TVP) which consists of 8 items.This study showed that the most ergonomic posture often overlooked when performing treatment procedures is backposition performed by 51 respondents (65.4%). Positioning the feet in such a way that the angle between the thigh and calf form the angle of 110Âº or more is the most rarely overlooked, just 19 respondents (24.4%). In this study, 39respondents (50%)were categorized as sufficient, which means50% of ergonomic stance/posture has been applied. It wasconcluded that ergonomic posture applied by clinical dental students of Hasanuddin University during treatmentprocedure was categorized as adequate.